Evidence for a Nonendosomal Function of the Saccharomyces cerevisiae ESCRT-III-Like Protein Chm7. Issue 4 (26th October 2015) - Bauer, Iva; Brune, Thomas; Preiss, Richard; Kölling, Ralf
Abstract: Endosomal sorting complex required for transport (ESCRT) proteins are involved in a number of cellular processes, such as endosomal protein sorting, HIV budding, cytokinesis, plasma membrane repair, and resealing of the nuclear envelope during mitosis. Here we explored the function of a noncanonical member of the ESCRT-III protein family, the Saccharomyces cerevisiae ortholog of human CHMP7. Very little is known about this protein. In silico analysis predicted that Chm7 (yeast ORF YJL049w ) is a fusion of an ESCRT-II and ESCRT-III-like domain, which would suggest a role in endosomal protein sorting. However, our data argue against a role of Chm7 in endosomal protein sorting. The turnover of the endocytic cargo protein Ste6 and the vacuolar protein sorting of carboxypeptidase S (CPS) were not affected by CHM7 deletion, and Chm7 also responded very differently to a loss in Vps4 function compared to a canonical ESCRT-III protein. Our data indicate that the Chm7 function could be connected to the endoplasmic reticulum (ER). In line with a function at the ER, we observed a strong negative genetic interaction between the deletion of a gene function ( APQ12 ) implicated in nuclear pore complex assembly and messenger RNA (mRNA) export and the CHM7 deletion. The patterns of genetic interactions between the APQ12 deletion and deletions of ESCRT-III genes, two-hybrid interactions, and the specific localization of mCherry fusion proteins are consistent with the notion that Chm7 performs a novel function at the ER as part of an alternative ESCRT-III complex.